2017
DOI: 10.1097/md.0000000000008254
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of PCNA expression in patients with osteosarcoma

Abstract: Background:Numerous studies have attempted to determine the prognostic role of proliferating cell nuclear antigen (PCNA) expression in patients with osteosarcoma with no consistent conclusion. We performed this meta-analysis to systematically elucidate the association in a more precise manner.The purpose of this meta-analysis is to determine the prognostic role of PCNA in patients with osteosarcoma.Methods:A systematic search of relevant studies was performed in 6 electronic databases including PubMed, Embase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 24 publications
2
16
0
2
Order By: Relevance
“…More specifically, proliferating cell nuclear antigen (PCNA) has been shown to be an inhibitory ligand of natural cytotoxicity receptor NKp44 (21,22). It is also associated with poor prognosis in an analysis covering 16 studies with a total of 691 osteosarcoma patients (23). Osteosarcomas have been previously shown to express CD155 (Poliovirus Receptor, PVR) (24), which is one of the ligands for DNAX accessory molecule-1 (DNAM-1 or CD226), an activating receptor expressed on NK cells, monocytes and a subset of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, proliferating cell nuclear antigen (PCNA) has been shown to be an inhibitory ligand of natural cytotoxicity receptor NKp44 (21,22). It is also associated with poor prognosis in an analysis covering 16 studies with a total of 691 osteosarcoma patients (23). Osteosarcomas have been previously shown to express CD155 (Poliovirus Receptor, PVR) (24), which is one of the ligands for DNAX accessory molecule-1 (DNAM-1 or CD226), an activating receptor expressed on NK cells, monocytes and a subset of T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian kami sebelumnya menggunakan jaringan kanker payudara mengungkapkan bahwa ekspresi gen histone deacetylase 2 (HDAC2) dan proliferating cell nuclear antigen (PCNA) ditemukan perbedaan signifikan setelah terapi neoajuvan hormon dan kemoterapi. Penelitian ini bertujuan untuk menganalisis hubungan antara ekspresi HDAC2 dan PCNA dengan kelangsungan hidup sel punca kanker payudara dengan penanda aldehyde dehydrogenase + (ALDH+) yang diberi perlakuan endoksifen.Metode: Sampel adalah BCSC primer manusia ALDH+ yang diberi perlakuan endoksifen 4 uM masingmasing selama 2,4,6,8,10,12,14 hari. Viabilitas sel dilihat dengan menggunakan trypan blue dan ekspresi mRNA HDAC2 dan PCNA ditentukan menggunakan qRT-PCR.Hasil: Viabilitas BCSCs ALDH + menurun setelah 2 sampai 4 hari pemberian endoksifen.…”
unclassified
“…Metode: Sampel adalah BCSC primer manusia ALDH+ yang diberi perlakuan endoksifen 4 uM masingmasing selama 2,4,6,8,10,12,14 hari. Viabilitas sel dilihat dengan menggunakan trypan blue dan ekspresi mRNA HDAC2 dan PCNA ditentukan menggunakan qRT-PCR.…”
unclassified
“…CCNB1 and CDK1 have been found to regulated drug sensitiveness not only through cell cycle pathway, but p53 pathway according to our analysis. Previous study also found that PCNA was associated with cancers development [22,23] and patients prognosis [24,25] .…”
Section: Discussionmentioning
confidence: 74%